Students’ Conceptual Changes on the Air Pressure Learning Using Predict-Observe-Explain Strategy - Fuadi, Fitri Nurzakiah; Sopandi, Wahyu; Priscylio, Ghery; Hamdu, Ghullam; Mustikasari, Lidya (Universitas Pendidikan Indonesia, 2020)
The concept of air-having pressure needs to be understood by students so that they can understand natural phenomena related to the air concept. The characteristic of the abstract concept of air having pressure leads students to misconceptions. The purpose of this study is to analyze changes in students' conceptions of the air-having pressure concept by using the POE strategy. The research method used was a pre-experiment with one group pretest-posttest design. Pretest and posttest questions were given to students using the five-level diagnostic test instrument with a total of three questions. The ability to predict-test and the ability to observe-test were performed with four questions on each test. The participants of this study consisted of 31 fifth grade students in the even semester. The categorization of conception change is divided into five patterns: construction, revision, static, disorientation, and complementation. Based on the analysis, revision had the highest percentage followed by construction. The conclusion is that the POE strategy can help students in understanding the concept of air-having pressure so that there was a change from misconception to understanding scientific concepts.